Temporal Perceptual Cues of Velar and Bilabial Stop Consonants - Usha Rani P.N (Journal of All India Institute of Speech and Hearing, 1970)
Human speech perception is an area under study since several decades and still remains as an unsolved puzzle. With the emergence of knowledge onthe speech production differences in various languages, perceptual process are being studied in different languages of the world.The present study, aims to determine the effect of closure duration, preceding vowel duration, transition durations of preceding and following vowels and VOTon the perception of medial geminate unaspirated bilabial and velar stop consonants across the language groups of Kannada and Hindi.